2023
DOI: 10.3390/diagnostics13091552
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the RDW Index (Red Cell Distribution Width) in Women with Breast Cancer Treated with Doxorubicin in a One-Year Follow-Up Study

Abstract: Breast cancer is the most common cancer and the most frequent cause of death in women. Doxorubicin, an anthracycline, is an important drug due to its efficacy in treating solid cancers, especially breast cancer. However, this drug is often responsible for cardiotoxicity that may affect more than 25% of patients. This study aimed to evaluate the red cell distribution width (RDW) in women with breast cancer to monitor adverse events associated with the use of doxorubicin. A prospective study of 80 women with bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…RDW could be used as a potential pre-treatment predictor of response in patients with BC and other malignancies. [ 31 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…RDW could be used as a potential pre-treatment predictor of response in patients with BC and other malignancies. [ 31 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…Complete blood count-based biomarkers have been shown to correlate well with clinical outcomes in numerous chronic [ 5 , 6 , 7 , 8 , 9 , 10 ], infectious [ 11 , 12 , 13 , 14 , 15 ], and surgical conditions [ 16 , 17 , 18 , 19 , 20 ], as well as in cancer [ 21 , 22 , 23 , 24 , 25 , 26 ]. In particular, the potential role of the red cell distribution width (RDW), a biomarker of the heterogeneity of red blood cells’ size, in predicting adverse events and survival currently represents a topic of intense research in numerous clinical conditions [ 27 , 28 ], including malignancies such as colorectal cancer [ 29 , 30 , 31 ], esophageal cancer [ 32 , 33 ], lung cancer [ 34 , 35 ], breast cancer [ 36 , 37 ], and other malignancies [ 38 , 39 , 40 , 41 , 42 ]. In addition, several studies have shown that alterations in the RDW correlate with liver function and prognosis in numerous hepatic cancer-predisposing conditions, such as hepatitis B, chronic liver disease, and fibrosis [ 43 , 44 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%